FRI0247 The Involvement of The Long Noncoding H19x in tGFβ Signaling and Its Profibrotic Effects in Systemic Sclerosis and Other Fibrotic Diseases. (15th July 2016) - Pachera, E.; Assassi, S.; Salazar, G.; Frank-Bertoncelj, M.; Dobrota, R.; Brock, M.; Kurreeman, F.; de Vries-Bouwstra, J.; Messemaker, T.; Feghali-Bostwick, C.; Distler, J.; Kania, G.; et al.
Abstract : Background: Long noncoding RNAs (lncRNAs) are an emerging class of noncoding transcripts involved in the regulation of gene expression in health and disease. We have recently identified a novel lncRNA, H19X, which is strictly regulated by TGFβ in a dose and time dependent manner. Objectives: To detail the differential expression of H19X in SSc and other fibrotic diseases and to characterize its function in fibrotic diseases. Methods: Skin and lung biopsies from patients with SSc, idiopathic lung fibrosis (IPF), and healthy controls (HC) were obtained from cohorts at four different expert centers. Expression of H19X was analyzed by RNA Sequencing Ilumina HiSeq2000 and real-time PCR respectively. H19X was silenced in skin fibroblasts using locked nucleic acid antisense oligonucleotides (LNA GapmeRs), followed by qPCR analyses, immunofluorescence staining, SIRCOL assay, contraction assay and Western blot. In situ hybridization of H19X on SSc dermal fibroblast was performed using Stellaris FISH probes. Results: H19X expression was consistently upregulated across all four cohorts (SSc n=34, HC n=26). Notably, the upregulation was also consistent across different subsets of patients. H19X showed a similar expression profile in clinically non-involved skin compared to established fibrotic skin. Moreover, expression of H19X was also significantly increased in SSc interstitial lung disease patients versus HC (n=11 each, p<0.05). A significant H19X overexpression was also detected in IPF samples indicating a broader role of H19X in fibrotic diseases (n=11 each, p<0.05). The knockdown of H19X by GapmeRs in skin fibroblasts led to a strong downregulation of collagen 1, fibronectin and αSMA mRNAs (n=5, p<0.05). Furthermore, H19X knockdown followed by SIRCOL assay and Western blot analysis confirmed the importance of this lncRNA in the regulation of extracellular matrix components such as collagens and fibronectin. Additionally, silencing of H19X significantly impaired αSMA fiber formation, stress fiber formation and cell contractility showing an important role of H19X in the development of the myofibroblast phenotype. Because the H19X gene hosts the sequence for two microRNAs, miR-424 and miR-503, it could exert its function acting as reservoir for these microRNAs. However, the effects of miR-503 and miR-424 loss and gain of function experiments on fibrosis measures were minimal compared to the effects after H19X silencing indicating that H19X employs another main molecular mechanism. Indeed, in situ hybridization showed that TGFβ-induced expression of H19X is localized to a defined spot in the nucleus indicating that H19X could influence gene expression by directly interacting with the chromatin. Conclusions: H19X is a novel lncRNA which is a key factor in mediating the pro-fibrotic effects of TGFβ in systemic sclerosis and other fibrotic diseases. Disclosure of Interest: E. Pachera: None declared, S. Assassi: None declared, G. Salazar: None declared, M. Frank-Bertoncelj: None declared, R. Dobrota: None declared, M. Brock: None declared, F. Kurreeman: None declared, J. de Vries-Bouwstra: None declared, T. Messemaker: None declared, C. Feghali-Bostwick: None declared, J. Distler: None declared, G. Kania: None declared, O. Distler Grant/research support from: from Bayer, Sanofi, Ergonex, Boehringer Ingelheim, Actelion, Pfizer, Consultant for: from 4 D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, EpiPharm, Ergonex, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, MedImmune, Pharmacyclics, Pfizer, Serodapharm, Sinoxa,